LAUGHTER OUT OF PLACE: AFFECTIVE HOMOPHILY AND THE ABSURD COMEDY OF #METOO - Sundén, Jenny; Paasonen, Susanna (AoIR Selected Papers of Internet Research, 2019)
This paper investigates the affective and ambiguous dynamics of feminist humor as an unexpected strategy of resistance in connection with #MeToo, asking what laughter may do to the sharpness of negative affects of shame and anger driving the movement. Firstly, we deploy Nanette—Hannah Gadsby’s 2018 Netflix success heralded as the comedy of the #MeToo era—arguing that the uniform viral warmth surrounding the show drives the emergence of networked feminisms through “affective homophily,” or a love of feeling the same. With Nanette, the contagious qualities of laughter are tamed by a networked logic of homophily, allowing for affective intensity while resisting dissent in what is being felt. Secondly, and as a counter force to such sameness, we examine absurd feminist humor trafficking in the unreasonable, illogical, and inappropriate. In considering the unexpected pockets of humor within the #MeToo scandal that ripped apart the prestigious institution of the Swedish Academy in 2018, we explore the emergence of absurdist feminist comedy by zooming in on the figure of the unseemly woman and humor that is knowingly out of tune with both reason and decency. While our first example allows us to argue for the political importance of affective ambiguity, difference, and dissent in social media feminisms, our second example opens up a space for affective release that unpredictable and surprising absurd humour, in combining the illogical with the indecent, affords.